Magical Realism and Cosmopolitanism Strategizing Belonging - Sasser, K. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Magical Realism and Cosmopolitanism details a variety of functionalities of the mode of magical realism, focusing on its capacity to construct sociological representations of belonging. This usage is traced closely in the novels of Ben Okri, Salman Rushdie, Cristina García, and Helen Oyeyemi.